2022
DOI: 10.3390/nu14173591
|View full text |Cite
|
Sign up to set email alerts
|

Do Vegetarian Diets Provide Adequate Nutrient Intake during Complementary Feeding? A Systematic Review

Abstract: During the complementary feeding period, any nutritional deficiencies may negatively impact infant growth and neurodevelopment. A healthy diet containing all essential nutrients is strongly recommended by the WHO during infancy. Because vegetarian diets are becoming increasingly popular in many industrialized countries, some parents ask the pediatrician for a vegetarian diet, partially or entirely free of animal-source foods, for their children from an early age. This systematic review aims to evaluate the evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 56 publications
1
25
0
Order By: Relevance
“…The most affordable iron-rich foods according to price modeling approaches are dark-green leafy vegetables [ 101 ]. Some evidence suggests that vegetarian diets that are varied and nutritionally adequate rarely result in iron and zinc deficiencies [ 102 , 103 , 104 ]. However, there is also evidence arguing that vegetarian and vegan diets are not safe and can result in micronutrient deficiencies which in turn can affect the brain development of the child [ 105 , 106 , 107 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most affordable iron-rich foods according to price modeling approaches are dark-green leafy vegetables [ 101 ]. Some evidence suggests that vegetarian diets that are varied and nutritionally adequate rarely result in iron and zinc deficiencies [ 102 , 103 , 104 ]. However, there is also evidence arguing that vegetarian and vegan diets are not safe and can result in micronutrient deficiencies which in turn can affect the brain development of the child [ 105 , 106 , 107 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent prospective cohort study in Thailand (a middle income country (MIC)) reported that protein from formula and cow's milk had greater impact on infant weight gain during the CF period than protein from non-dairy ASF, while growth parameters were not associated with plant-based protein intake [22 ▪ ]. A SR/ MA also reported no effect of plant-based diets during CF on weight gain or obesity risk, although these diets may increase the risk of micronutrient insufficiency/deficiency and growth faltering [23 ▪ ].…”
Section: Complementary Food Content and Dietary Patternsmentioning
confidence: 99%
“…A recent systematic review that examined adequate nutrient supply of vegetarian and vegan diets during complementary feeding concluded that diets that avoid or severely limit animal-based foods were not safe [ 18 ]. The available evidence suggested that the risk of deficiency of critical nutrients and growth retardation was high.…”
Section: A Vegan Lifestyle Requires Knowledge and Active Managementmentioning
confidence: 99%